An analysis of the value of public opinion on politics amongst young adults in Singapore. - Phua, Delia Mei Ting. (2009)
Investigating the value of offering public opinions on politics in Singapore held by young Singaporean adults, I wanted to explore if these young Singaporean adults hold any form of negative values or negatively associated connotations in offering their opinions on politics in Singapore. Through in-depth interviews with my respondents and drawing on the concepts of power and hegemony and the ideologies of pragmatism and meritocracy, in this paper, I argue that through consensual and coercive means of control, the ruling political party, the People’s Action Party (PAP), has been able to maintain and legitimize its hegemonic hold on power over Singapore politics. The resulting displays of political engagement, or lack thereof, is in effect a result of a populace that is sanitized to the idea of material contentment that is void of political repercussions.